BETWEEN CALAMITY AND COMMUNICATION: THE ROLE OF BROADCAST MEDIA IN THE 2014 KASHMIR FLOODS - Hidayat, Tasaduq; Hassan, Ruheela (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The media continues to have significant relevance in crises as they play an essential role in guiding the state’s response toward reconstruction and rehabilitation. Although there has been a phenomenal advancement in media systems, the existing literature suggests that the media impact has either been ineffective or minimal in post-disaster scenarios. This study aims to assess the media reaction during post-disaster scenarios and to understand if the media convergence sufficiently influences the state action and policy toward disaster preparedness and mitigation. In this direction, this research undertakes the case study of the 2014 Kashmir flood to examine the role played by electronic media in disaster management. Interviews of working journalists, academicians, and scholars were conducted to study electronic media’s response during the crisis. Additionally, the document analysis, as a secondary source, has helped in understanding the crucial situations during different natural disasters. The inferences and conclusions from the study would guide further research into conceptualizing a mechanism for the development of a sustainable media policy to meet the sustainable development goal.